2005
DOI: 10.1016/j.cmet.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Insig-mediated degradation of HMG CoA reductase stimulated by lanosterol, an intermediate in the synthesis of cholesterol

Abstract: Feedback control of cholesterol synthesis is mediated in part by sterol-induced binding of HMG CoA reductase to Insig proteins in the endoplasmic reticulum (ER). Binding leads to ubiquitination and proteasomal degradation of reductase, a rate-controlling enzyme in cholesterol synthesis. Using in vitro and in vivo assays, we show that lanosterol, the first sterol intermediate in cholesterol synthesis, potently stimulates ubiquitination of reductase, whereas cholesterol has no effect at 10-fold higher concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
231
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(244 citation statements)
references
References 42 publications
10
231
2
1
Order By: Relevance
“…HMGCoAR is the rate-limiting enzyme of cholesterol synthesis, yet surprisingly, low cholesterol levels provide only a relatively weak feedback effect on HMGCoAR. 34 HMGCoAR is under highly complex regulation, 35 but a critical regulator is feedback through the direct sterol-sensing of the lanosterol level (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGCoAR is the rate-limiting enzyme of cholesterol synthesis, yet surprisingly, low cholesterol levels provide only a relatively weak feedback effect on HMGCoAR. 34 HMGCoAR is under highly complex regulation, 35 but a critical regulator is feedback through the direct sterol-sensing of the lanosterol level (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…26 Through a complex, endoplasmic reticulum-based process, low lanosterol signals to decrease proteolysis of HMGCoAR, which results in increased cholesterol synthesis. 26,34 However, in the setting of normal lanosterol levels, such as observed in HCV infection, HMGCoAR proteolysis continues, and cholesterol synthesis is not up-regulated through this important pathway. Thus, with normal lanosterol levels, irrespective of cholesterol levels, the host fails to engage direct-sensing compensatory cholesterol synthesis through the rate-limiting step of HMGCoAR.…”
Section: Discussionmentioning
confidence: 99%
“…As with the SREBPs and other proteins, HMGR is targeted for degradation once it is ubiquitinated [41,56]. While HMGR can be ubiquinated in the presence of sterol [41], it is further ubiquinated in the presence of both sterol plus geranylgeraniol, implying involvement of a geranylgeranylated protein [57], or plus lanosterol [58]. These more recent data support the observations that maximal suppression of sterol synthesis rates occurs only in the presence of cholesterol plus a mevalonate-derived product [18,59], which may be absent in a tissue in a negative sterol balance and/or proliferating rapidly as during development [49].…”
Section: Hmgr Degradationmentioning
confidence: 99%
“…5 shows experiments in which we examined whether the D205A mutation also abolishes the ability of Insig-1 to accelerate the degradation of HMG CoA reductase. Studies have shown (5,17) that Insig-mediated degradation is triggered by the combined action of a sterol (25-HC or lanosterol) and a nonsterol isoprenoid (geranylgeraniol) derived from mevalonate. We cotransfected WT CHO-K1 cells with a plasmid encoding WT or the D205A mutant of Insig-1 together with a plasmid encoding the NH 2 -terminal membrane-spanning domain of HMG CoA reductase [HMG CoA reductase(TM1-8)].…”
Section: Figurementioning
confidence: 99%